Transformerless Inverter Topologies for Single-Phase Photovoltaic Systems: A Comparative Review - Khan, Md Noman H.; Forouzesh, Mojtaba; Siwakoti, Yam P.; Li, Li; Kerekes, Tamas; Blaabjerg, Frede (IEEE journal of emerging and selected topics in power electronics, 2020)
In photovoltaic (PV) applications, a transformer is often used to provide galvanic isolation and voltage ratio transformations between input and output. However, these conventional iron- and copper-based transformers increase the weight/size and cost of the inverter while reducing the efficiency and power density. It is therefore desirable to avoid using transformers in the inverter. However, additional care must be taken to avoid safety hazards such as ground fault currents and leakage currents, e.g., via the parasitic capacitor between the PV panel and ground. Consequently, the grid connected transformerless PV inverters must comply with strict safety standards such as IEEE 1547.1, VDE0126-1-1, EN 50106, IEC61727, and AS/NZS 5033. Various transformerless inverters have been proposed recently to eliminate the leakage current using different techniques such as decoupling the dc from the ac side and/or clamping the common mode (CM) voltage (CMV) during the freewheeling period, or using common ground configurations. The permutations and combinations of various decoupling techniques with integrated voltage buck-boost for maximum power point tracking (MPPT) allow numerous new topologies and configurations which are often confusing and difficult to follow when seeking to select the right topology. Therefore, to present a clear picture on the development of transformerless inverters for the next-generation grid-connected PV systems, this paper aims to comprehensively review and classify various transformerless inverters with detailed analytical comparisons. To reinforce the findings and comparisons as well as to give more insight on the CM characteristics and leakage current, computer simulations of major transformerless inverter topologies have been performed in PLECS software. Moreover, the cost and size are analyzed properly and summarized in a table. Finally, efficiency and thermal analysis are provided with a general summary as well as a technology roadmap.